2023
DOI: 10.1037/tra0001522
|View full text |Cite
|
Sign up to set email alerts
|

The Ukraine–Russia war: A symptoms network of complex posttraumatic stress disorder during continuous traumatic stress.

Abstract: Objective: This study is aimed to test the symptoms network of International Classification of Diseases, 11th Revision (ICD-11) complex posttraumatic stress disorder (CPTSD) symptoms, using data collected from Ukrainian civilians during the 2022 Russia-Ukraine war. Findings can inform our understanding of the stress response in individuals exposed to continuous trauma and give insight into the nature of CPTSD during the war. Method: A network analysis was conducted on CPTSD symptoms as assessed by the Internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…This may indicate that subjective sensation such as itch is not a crucial acne symptom during with the period of the military conflict. Recently, several authors have shown that the military conflict in Ukraine causes continuous traumatic stress to Ukrainian civilians [8,29] as well as within civilian populations in different countries [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may indicate that subjective sensation such as itch is not a crucial acne symptom during with the period of the military conflict. Recently, several authors have shown that the military conflict in Ukraine causes continuous traumatic stress to Ukrainian civilians [8,29] as well as within civilian populations in different countries [30].…”
Section: Discussionmentioning
confidence: 99%
“…Acne may also be classified as a psychophysiological disorder, which is exacerbated by psychological stress [7]. It is obvious that the military conflict in Ukraine is experienced by people as acute and chronic stress [8]. Several dermatological diseases, including chronic inflammatory ones like psoriasis, have been reported to be exacerbated during the war [9].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the reduction of PTSD symptoms among a country's civilian population and arriving migrants is influenced by such subject-social factors as socioeconomic status, sense of self-efficacy, confidence in rulers, and personal and national resilience (Goodwin et al, 2023;Kaniasty et al, 2023;Levin et al, 2023;Turrini et al, 2019). Results of research with civilian victims of war show that the vast majority of respondents demonstrate such resilience (Bonanno, 2021).…”
Section: Reactions To Threats Associated With War Traumamentioning
confidence: 99%
“…Хоча сучасні досягнення в галузі медицини й хірургії призвели до значного покращення показників виживаності після тяжких травм, стратегії реабілітації постраждалих осіб повинні бути адаптовані до сучасних умов. Реабілітація поранених у бойових діях потребує інтеграції кількох https://emergency.zaslavsky.com.ua Науковий огляд / Scientific Review професійних дисциплін для оптимального вирішення складних медичних і хірургічних завдань, а також унікальних психосоціальних факторів для того, щоб виправдати очікування пацієнтів, сімей, влади й суспільства [7][8][9][10][11][12].…”
Section: ключові слова: бойова хірургічна травма; посттравматичний ст...unclassified